Preparing for an aging Australia: The development of multidisciplinary core competencies for the Australian health and aged care workforce. Issue 3 (3rd July 2021) - Poulos, Roslyn G.; Boon, Mei Ying; George, Ajesh; Liu, Karen P. Y.; Mak, May; Maurice, Christina; Palesy, Debra; Pont, Lisa G.; Poulos, Christopher J.; Ramsey, Sarah; Simpson, Paul; Steiner, Genevieve Z.; et al.
ABSTRACT: Appropriately skilled staff are required to meet the health and care needs of aging populations yet, shared competencies for the workforce are lacking. This study aimed to develop multidisciplinary core competencies for health and aged care workers in Australia through a scoping review and Delphi survey. The scoping review identified 28 records which were synthesized through thematic analysis into draft domains and measurable competencies. Consensus was sought from experts over two Delphi rounds (n = 111 invited; n = 59 round one; n = 42 round two). Ten domains with 66 core competencies, to be interpreted and applied according to the worker's scope of practice were finalized. Consensus on multidisciplinary core competencies which are inclusive of a broad range of registered health professionals and unregistered aged care workers was achieved. Shared knowledge, attitudes, and skills across the workforce may improve the standard and coordination of person-centered, integrated care for older Australians from diverse backgrounds.